Synthesis and characterization of green tea paste nanoparticles based on wet milling - Yuly Peristiowati; Zauhani Kusnul (Wolters Kluwer Medknow Publications, 2020)
This study aims to analyze the synthesis of green tea herbs in the nanoform. Green tea is divided into three grades, namely Grade A, B, and C. Making pasta samples is done by wet milling technique. The tea paste sample was characterized by particle size analyzer and scanning electron microscope methods. Grade A green tea has a grain size of 77,014 ± 50,759 nm. Grade B green tea has a particle size of 12,987 ± 7,674 nm. Grade C green tea has a particle size of 4409 ± 5379 nm. It was concluded that the difference in grade of green tea determines the structure and size of the particles formed. Thus, the wet milling technique can be an alternative in making green tea nanoparticles for industrial scale.